The Effect of Zakat, Infaq and Sadaqah (ZIS) Funds on Economic Growth with Poverty Level as an Intervening Variable - Sastraningsih, Ellyan; Suryadi, Nanda; Fizari Abu Hassan Asari, Fadli (IKONOMIKA, 2025)
This study examines the relationship between economic growth and poverty levels in Indonesia in relation to zakat, infaq and sadaqah (ZIS) funds over a five-year period from 2018 to 2022. Zakat, infaq and sadaqah (ZIS) significantly contribute to economic growth. Zakat can improve people's welfare. It can help people who lack the resources to meet their basic needs. This research employs quantitative techniques and SEM Smart PLS analysis. Non-probability sampling with saturated samples was used. The research results show a significant influence of ZIS on economic growth. Poverty significantly affects economic growth. ZIS significantly affects economic growth with poverty as a mediating variable. Effective ZIS management by zakat institutions is expected to foster empowerment programmes that directly benefit the community. Strong cooperation between stakeholders to optimise ZIS fund collection can improve community welfare.